Regularities of mechanical behavior of steel 40Cr during the postcritical deformation of specimens in condition of necking effect at tension (Fracture and Structural Integrity, 2017)
The work is devoted to the experimental study of mechanical behavior regularities of the structural steel 40Cr under postcritical deformation of specimens in conditions of strain localization formation in the form of neck during extension. The results of testing specimens cut from the initial samples with a neck are given. Various levels of preliminary postcritical deformation of initial samples are implemented. Using a noncontact 3D video system for recording displacement and strain fields of Vic 3D Correlated Solutions, based on the digital images correlation technique, the displacement and strain fields in the gauge length of both the original specimens with the neck and after the groove were recorded in two different schemes to eliminate geometrical heterogeneity. On the base of obtained results, the stiffness and strength of 40Cr steel were evaluated in a necked specimen at various stages of postcritical deformation. It is shown that the material in the peripheral areas of the gauge length of the sample is in a strengthened state, which does not depend on the degree of previously achieved postcritical deformation, and the strength of the material in the neck-forming zone on the initial specimens is thereby increased.
Keywords: Experimental mechanics; Postcritical deformation; Strain localization; Neck; Tension; Digital image correlation